A Future Vision for Procurement Software Use in Procurement Organisations - Kadowaki, Rintaro (2018)
Background – The role of procurement has been evolving towards strategic initiatives from administrative tasks as companies have become more aware of its importance, and procurement organisation has expanded its responsibilities in a company over decades. Along with the transition and expansion, software functionalities that support procurement function has advanced as well. Recently, the advancement of information technologies is remarkable such as artificial intelligence and robotic process automation (RPA). Under those circumstances, it can be assumed expectations for procurement software functionalities in leading procurement organisations have been evolving as well. As the research of such situation focuses on ongoing phenomenon, there is not much academic literature in this area yet.